Association Between Daily Average of Mobility Achieved During Physical Therapy Sessions and Hospital-Acquired or Ventilator-Associated Pneumonia among Critically Ill Patients. (May 2023) - Qi, Wei; Murphy, Terrence E.; Doyle, Margaret M.; Ferrante, Lauren E.
Purpose: Hospital-acquired and ventilator-associated pneumonias (HAP and VAP) are associated with increased morbidity and mortality. Immobility is a risk factor for developing ICU-acquired weakness (ICUAW). Early mobilization is associated with improved physical function, but its association with hospital-acquired (HAP) and ventilator-associated pneumonias (VAP) is unknown. The purpose of this study is to evaluate the association between daily average of highest level of mobility achieved during physical therapy (PT) and incidence of HAP or VAP among critically ill patients. Materials and Methods: In a retrospective cohort study of progressive mobility program participants in the medical ICU, we used a validated method to abstract new diagnoses of HAP and VAP. We captured scores on a mobility scale achieved during each inpatient physical therapy session and used a Bayesian, discrete time-to-event model to evaluate the association between daily average of highest level of mobility achieved and occurrence of HAP or VAP. Results: The primary outcome of HAP/VAP occurred in 55 (26.8%) of the 205 participants. Each increase in the daily average of highest level of mobility achieved during PT (0-6 mobility scale) exhibited a protective association with occurrence of HAP or VAP (adjusted hazard ratio [HR] 0.61; 95% CI 0.44, 0.85). Age, baseline ambulatory status, Acute Physiology and Chronic Health Evaluation (APACHE) II, and previous day's mechanical ventilation (MV) status were not significantly associated with the occurrence of HAP/VAP. Conclusions: Among critically ill patients in a progressive mobility program, a higher daily average of highest level of mobility achieved during PT was associated with a decreased risk of HAP or VAP.